A retrospective study on the oral health of patients in the intesive care unit - Diamantino, Laura Gusmão Soares; Monteiro, Briana Góes; Dantas, Juliana Borges de Lima; Reis, Sílvia Regina de Almeida; Medrado, Alena Peixoto (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: the oral condition of patients in the Intensive Care Unit (ICU) is extremely important for clinical status monitoring, as lesions in the oral mucosa may imply complications and worsening of the health status of these patients. A higher probability of adherence, colonization, and bacterial infection in the oral cavity of patients in the ICU has also been reported. The poor oral hygiene conditions of these patients may be related to the reduction of salivary flow and difficulties in maintaining oral hygiene in a hospital environment, which rarely employs dentists on staff. Objective: to analyze the dental condition of patients admitted to the ICU of Roberto Santos General Hospital, Salvador, Bahia, Brazil. Methodology: a total of 73 patients were evaluated through an oral examination performed with a wooden spatula and sterile gauze under natural light, and data were collected and analyzed. Results: the most commom oral lesions were tongue-coating (41%) and ulcerations in the oral mucosa caused by trauma or dehydration (19.1%). The occurrence of pseudomembranous candidiasis (8.2%), dehydration of the lips and mucosa (26%), and angular cheilitis (9.5%) was additionally recorded. It was observed that 31.5% patients had more than 10 days of hospitalization and of these, 26% presented pseudomembranous candidiasis. This clinical condition was not seen in patients with a shorter hospital stay. Conclusions: this study suggest a possible association between the length of stay of these patients and the clinical conditions presented. Thus, the results of this study may guide preventive and curative measures implemented by dental surgeons who may, in the future, be part of the multidisciplinary team of professionals working in the hospital environment, especially in ICUs.